INOVASI PENDIDIKAN BERBASIS TEKNOLOGI: ANALISIS PERBANDINGAN SISTEM PENDIDIKAN INDONESIA DAN SINGAPURA - Renhar; Taufik Mustofa; M. Makbul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The advancement of digital technology has driven the transformation of education systems in various countries, including Indonesia and Singapore. Although both nations have adopted technology in learning, there are differences in their levels of readiness, policies, and implementation effectiveness. This study aims to analyze and compare technology-based educational innovations in the Indonesian and Singaporean education systems and to identify the factors influencing successful implementation, serving as lessons for educational development in Indonesia. The study employs a literature review method with a descriptive qualitative approach. Data were gathered through an examination of various scholarly sources, including journal articles, books, government reports, and relevant academic publications. The findings indicate that Singapore has developed an integrated, technology-based education system through consistent policies, adequate digital infrastructure, and continuous teacher competency development. Meanwhile, Indonesia has pursued various innovations—such as education digitalization programs, the implementation of digital learning platforms, and the *Merdeka Belajar* (Freedom to Learn) policy—yet it continues to face challenges regarding infrastructure disparities, low digital literacy among educators, and uneven technology utilization across regions. The study concludes that strengthening policies, ensuring equitable digital infrastructure, and enhancing teacher capacity are strategic factors for accelerating technology-based educational transformation in Indonesia by adapting best practices from Singapore.